Virtual Reality in Gerontechnology: A Cross-Age Comparative Study Using Head-Mounted Displays - Christofoletti, Gustavo; Mello Floriano, Isabela; Melo Ribeiro, Maria Fernanda; Miziara Barbosa, Suzi Rosa (Estudos Interdisciplinares sobre o Envelhecimento, 2026)
Abstract: As Gerontechnology integrates digital innovations into aging-related contexts, understanding its biological and physiological implications becomes important. This study aimed to analyze postural control in older adults and determine whether the impact of virtual reality is greater in this population than in young adults. A total of 50 participants were evaluated: 25 older (68.9 ± 7.3 years) and 25 young (22.4 ± 1.7 years) adults. All participants were exposed to an immersive 3D roller coaster simulation using a head-mounted display. Postural control assessments were performed before and during exposure. The variables analyzed were frontal and lateral sway, center of pressure sway area, and corresponding speeds. Repeated-measures analysis of variance revealed a significant main effect of group, indicating poorer postural control in older adults. A main effect of task was observed in both groups for lateral sway and center of pressure sway area. No significant group × task interaction was found, confirming a similar impact of virtual reality between older and young adults. The findings indicate that virtual reality is a promising tool in Gerontechnology. However, it should be used with caution because of its impact on postural control.